"I Rebel, Therefore We Are" (Albert Camus): New Political Thinking on Individual Responsibility for Group, Society, Culture, and Planet. (April 2016) - Samuels, Andrew
This article is an attempt to open discussion on the role of the individual, as opposed to the group, in contemporary progressive and radical politics. The phrase making a difference comes to mind. Academic ideas about the contexts and groups in which individuals operate are important yet require extensive revision. Jung's ideas about the relationship of individuals and the social collective are useful as is Camus' (1951/1953) book The Rebel . This article presents new thinking about individuals as fractured and broken as distinct from the autonomous unit promulgated by neoliberal thinking. Yet they remain individuals.